2018
DOI: 10.1017/s0021859618000424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tributyrin supplementation on short-chain fatty acid concentration, fibrolytic enzyme activity, nutrient digestibility and methanogenesis in adult Small Tail ewes

Abstract: In vivo and in vitro trials were conducted to assess the effects of tributyrin (TB) supplementation on short-chain fatty acid (SFCA) concentrations, fibrolytic enzyme activity, nutrient digestibility and methanogenesis in adult sheep. Nine 12-month-old ruminally cannulated Small Tail ewes (initial body weight 55 ± 5.0 kg) without pregnancy were used for the in vitro trial. In vitro substrate made to offer TB at 0, 2, 4, 6 and 8 g/kg on a dry matter (DM) basis was incubated by ruminal microbes for 72 h at 39°C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…lactilyticas can hydrolyze TB as well as glycerol, and their mainly fermenting products were VFAs especially acetic acid, propionic acid but no formic or butyric acids [27]. Besides, our in vitro and in vivo studies have demonstrated that supplementing TB could signi cantly promote the concentration of total VFAs in both rumen and fermentation uids [11,[28][29][30]. Furthermore, a novel esterase gene made of uncultured microorganisms from the contents of cow rumen has been cloned [31].…”
Section: Discussionmentioning
confidence: 99%
“…lactilyticas can hydrolyze TB as well as glycerol, and their mainly fermenting products were VFAs especially acetic acid, propionic acid but no formic or butyric acids [27]. Besides, our in vitro and in vivo studies have demonstrated that supplementing TB could signi cantly promote the concentration of total VFAs in both rumen and fermentation uids [11,[28][29][30]. Furthermore, a novel esterase gene made of uncultured microorganisms from the contents of cow rumen has been cloned [31].…”
Section: Discussionmentioning
confidence: 99%
“…For weaned Small-Tailed Han sheep, supplementing TB was observed to enhance the relative abundances of rumen bacteria at both the phylum and genus levels [10]. Besides, our previous experiments demonstrated that TB supplementation could significantly increase the yield of microbial crude protein and promote volatile fatty acids concentration in both rumen and fermentation fluids [11][12][13][14]. It is well known that the rumen microbial composition plays a vital role in both the growth and production of ruminant animals through its association with rumen bacteria; thus, we hypothesized that adding TB to the diet had a good potential to improve the meat quality characteristics such as amino acid (AA) content and FA level in mutton.…”
Section: Introductionmentioning
confidence: 94%